2022
DOI: 10.21203/rs.3.rs-1293562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salidroside attenuates HALI via IL-17A-mediated ferroptosis of alveolar epithelial cells by regulating Act1-TRAF6-p38 MAPK pathway

Abstract: Background and Purpose: Hyperoxia-induced acute lung injury (HALI) is a critical life-threatening disorder characterized by severe infiltration immune cells and death of type II alveolar epithelial cells (AECII). However, little is known about the relations between immune cells and AECII in HALI. IL-17A is a pro-inflammatory cytokine mainly secreted by Th17 cells, contributing to the pathogenesis of various inflammatory diseases. The present study investigated the role of IL-17A in cell-cell communication betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We determined that the expression levels of SP-C and T1α protein in the lung tissue of mice with BPD induced by hyperoxia were decreased, implying that alveolar epithelial cells were damaged and AECII trans-differentiation was abnormal. Long-term exposure to hyperoxia can induce a pro-inflammatory response in lung tissue, manifesting as the increase of various inflammatory factors and the apoptosis of alveolar epithelial cells [44, [46]. We determined that the levels of IL-17 A and IL-6 in the lung tissue of the hyperoxia group were remarkably increased, suggesting that the inflammatory response mediated by IL-17 A and IL-6 affected the process of AECII trans-differentiation and alveolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined that the expression levels of SP-C and T1α protein in the lung tissue of mice with BPD induced by hyperoxia were decreased, implying that alveolar epithelial cells were damaged and AECII trans-differentiation was abnormal. Long-term exposure to hyperoxia can induce a pro-inflammatory response in lung tissue, manifesting as the increase of various inflammatory factors and the apoptosis of alveolar epithelial cells [44, [46]. We determined that the levels of IL-17 A and IL-6 in the lung tissue of the hyperoxia group were remarkably increased, suggesting that the inflammatory response mediated by IL-17 A and IL-6 affected the process of AECII trans-differentiation and alveolarization.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to hyperoxia, IRF4-KO mice exhibit a higher proportion of FOXP3 + Treg as the predominant phenotype in lung tissue, leading to a more effective inhibitory function. FOXP3 + Treg can promote the normal proliferation and differentiation of lung epithelial cells, inhibit lung inflammation, and resolve acute lung injury [17,46]. It can be concluded that knocking out IRF4 can inhibit the phenotype switching of Tregs in the lung tissue of mice induced by hyperoxia, thereby reducing inflammatory response and alveolar epithelial cell damage.…”
Section: Discussionmentioning
confidence: 99%